The Role Of Mediation Based On Regulation Of The Minister Of Agrarian And Spatial Planning/Head Of The National Land Agency Number 21 Of 2020 Concerning The Handling And Settlement Of Land Cases - Yusri, Muhamad; Moonti, Roy Marthen; Ahmad, Ibrahim; Kasim, Muslim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Settlement of land cases through mediation carried out by the Land Office of Boalemo Regency refers to Regulation of Agrarian Affairs Minister and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases. Mediation as an alternative for resolving land cases, it is necessary to popularize